Chapter 13. Pepper Production - Peter J. Dittmar; Phillip B. Williams; Craig Frey; Eugene J. McAvoy; Johan Desaeger; Gary E. Vallad; Nathan S. Boyd (EDIS)
Chapter 13 of the Vegetable Production Handbook.